Connecting intersectionality and reflexivity: methodological approaches to social positionalities - Carstensen-Egwuom, Inken (ERDKUNDE, 2014)
Intersectional approaches to social positionalities have stressed the interdependence between different kinds of social divisions as well as the relational nature of social categories. In empirical research practice, these complexities require a high level of methodological reflexivity. In this paper, I will show how different kinds of methodological reflexivity are connected to the concept of intersectionality. Reflexivity includes continuous attention and reflection upon the social practices of positioning and differentiation in the field (including the positioning of the researcher), as well as analytic reflection upon the importance of academic knowledge and processes for social and political struggles. Using empirical examples from fieldwork with West African migrants in Bremen, I will show how important insights into the processes of social category-making and the importance of locality and space for intersectional social positioning can be derived from reflexive analytic practices.